Constitutionalism and Democratic Backsliding: A Normative Analysis of Contemporary Governance Trends - Mappasessu Mappasessu; Erniati Erniati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This article develops a normative-doctrinal framework for assessing democratic backsliding within contemporary constitutional governance. Departing from purely descriptive accounts of institutional decline, the study reconstructs constitutionalism as a principled architecture grounded in separation of powers, judicial independence, electoral equality, emergency limitation, and administrative neutrality. Through comparative constitutional analysis across federal, unitary, and multilevel systems, the research demonstrates that democratic regression frequently occurs through formally lawful amendments, statutory reforms, and regulatory recalibrations that preserve textual compliance while undermining substantive democratic guarantees. By synthesizing scholarship on executive aggrandizement, populist constitutionalism, supranational oversight, and emergency governance, the article articulates evaluative benchmarks capable of distinguishing adaptive constitutional reform from erosive transformation. The study further advances the concept of constitutional repair as a doctrinal mechanism for restoring institutional equilibrium. Its contribution lies in integrating normative reconstruction with comparative constitutional methodology to generate analytically rigorous and generalizable standards for diagnosing and responding to democratic backsliding in the twenty-first century.